Edukasi Pencegahan Virus Corona (COVID-19) dan Donasi Masker untuk Kesehatan Masyarakat di Kelurahan Jati, Kota Padang - Azrimaidaliza Azrimaidaliza; Septia Pristi Rahmah; Nadia Chalida Nur; Novia Wirna Putri; Siti Nur Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
COVID-19 cases in West Sumatra have shown a significant increase in the past month. To accelerate the handling of COVID-19, the government implemented Large-Scale Social Restrictions started on April 22, 2020. Enforcement is also carried out in Padang which has the highest number of COVID-19 cases with 107 positive confirmed cases with 12 deaths. Efforts to prevent the spread of this virus can be carried out through collaborative community service activities between educational institutions and urban villages in Padang City. One of these activities was community service activities held in Jati, East Padang District, Padang City, namely through educational activities using leafleat and posters as promotion media then also donating masks to improve people's healthy behavior. Promotional media were distributed to the public due to situations that make it impossible to carry out activities by gathering many people in one place. The activity went well, received a good response from the village head and all village officials. Media and donations were distributed by the village head especially for poor families and low access to information. Monitoring and evaluation were needed from the village and service providers in increasing the implementation of healthy behavior by the community.